EFEKTIFITAS PERANGKAT PEMBELAJARAN FISIKA MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS MATERI ELASTISITAS - Ika Astutik, Fitriyah; Fajriyah (Universitas Tadulako, 2021)
This study aim of this study is to find out how effective the Project Based Learning (PjBL) model of physics learning tools is to improve students' Science Process Skills. The learning tools developed include: (a) syllabus, (b) lesson plans, (c) student books, (d) worksheets, and (e) assessment sheets. This type of research is Research Design that aims to develop learning tools. The research design used was a one-group pretest-posttest design. The learning device developed has been tested on class XI students of SMA An-Nidhomiyah Pamekasan in the odd semester of the 2016-2017 school year on the concept of Elasticity of Materials. The research parameter measured was the effectiveness of the Project-Based Learning model of physics learning tools to improve students' Science Process Skills. The instruments used to collect data in this study include Affective Observation Sheets, Product Cognitive Learning Outcomes Test Instruments, Process Cognitive Learning Outcomes Test Instruments, Psychomotor Observation Instruments, Student Response Questionnaire Instruments. The results of the research that have been carried out show that (a) the learning tools developed are effectively used to improve students' Science Process Skills, (b) the product cognitive learning outcomes and students' cognitive processes have increased significantly, and (c) students provide a positive response to the learning that has been implemented. So it can be concluded that the learning tools developed to meet the criteria of effectiveness so that the learning tools are effective for improving students' science process skills.